Essential Role of the Zinc Finger Transcription Factor Casz1 for Mammalian Cardiac Morphogenesis and Development - Liu, Zhihui (American Society for Biochemistry and Molecular Biology, 2014)
Chromosome 1p36 deletion syndrome is one of the most common terminal deletions observed in humans and is related to congenital heart disease (CHD). However, the 1p36 genes that contribute to heart disease have not been clearly delineated. Human CASZ1 gene localizes to 1p36 and encodes a zinc finger transcription factor. Casz1 is required for Xenopus heart ventral midline progenitor cell differentiation. Whether Casz1 plays a role during mammalian heart development is unknown. Our aim is to determine 1p36 gene CASZ1 function at regulating heart development in mammals. We generated a Casz1 knock-out mouse using Casz1-trapped embryonic stem cells. Casz1 deletion in mice resulted in abnormal heart development including hypoplasia of myocardium, ventricular septal defect, and disorganized morphology. Hypoplasia of myocardium was caused by decreased cardiomyocyte proliferation. Comparative genome-wide RNA transcriptome analysis of Casz1 depleted embryonic hearts identifies abnormal expression of genes that are critical for muscular system development and function, such as muscle contraction genes TNNI2, TNNT1, and CKM; contractile fiber gene ACTA1; and cardiac arrhythmia associated ion channel coding genes ABCC9 and CACNA1D. The transcriptional regulation of some of these genes by Casz1 was also found in cellular models. Our results showed that loss of Casz1 during mouse development led to heart defect including cardiac noncompaction and ventricular septal defect, which phenocopies 1p36 deletion syndrome related CHD. This suggests that CASZ1 is a novel 1p36 CHD gene and that the abnormal expression of cardiac morphogenesis and contraction genes induced by loss of Casz1 contributes to the heart defect.